Air quality modelling system over a central mediterranean region - Schipa, Ilenia (2002)
This work presents a complex modelling system for air quality studies. The system couples meteorological models, emission preprocessors and dispersion models. Two meteorological models have been coupled in cascade: a mesoscale meteorological model and a 3D diagnostic micro-meteorological model, which is able to provide a realistic three-dimensional wind and temperature fields and two dimensional fields of boundary layer parameters. The emission data were obtained trough disaggregation of national emission inventory, by using a database related to all industrial sources, and through direct evaluation of road transport and biogenic emissions. Meteorological fields and emission data have been used by a photochemical model and by a Lagrangian puff dispersion model. The modelling system has been applied over Salento Peninsula, located in the south-east corner of Italy, in the Mediterranean central area in a real typical summer scenario.